Renal primitive neuroectodermal tumor (RPNET) in children (Journal of Paediatric Surgeons of Bangladesh, 2018)
Renal primitive neuroectodermal tumor (rPNET) as a member of Ewing’s sarcoma family is extremely rare and usually occurs in children and young adults. Most literature about rPNET was isolated case reports. Here we described a case of renal PNET in a 7-year-old girl who presented at our Paediatric Surgery Department of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh with fever, left flank pain and mass Ultrasonogram (USG) and Computer tomography (CT) scan revealed a huge mass in the left kidney. The patient underwent left radical nephrectomy with neoadjuvent chemotherapy on April,2016. Histopathology and immunohistochemistry (IHC) confirmed the diagnosis of PNET. She did not receive adjuvant chemotherapy, as advised. She had a local tumor recurrence 3 months after the surgery and continued to deteriorate but not developed distant metastasis. She again received 2-cycle of chemotherapy but size did not decrease. So re-do surgery was performed on 10.01.2017 and send to paediatric haemato-oncology department of BSMMU for further management. rPNET is rare and presents aggressive clinical behavior and worse prognosis. We expect that further awareness and study of this rare tumor can be had by presenting our case.Journal of Paediatric Surgeons of Bangladesh (2016) Vol. 7 (2): 66-71